44 single institutional experience of interrupted aortic arch repair asad khan, mohamed elrih, yamin alzain, prof mark redmond, jonathan mcguinness, lars nolke. paediatric cardiothoracic surgery unit, our lady's children's hospital crumlin dublin. (5th October 2017) - Khan, A; Elrih, M; McGuinnes, J; Nolke, L; Redmond, M
Abstract : Introduction: Interrupted aortic arch (IAA) is a rare congenital heart disease and is often associated with other cardiovascular anomalies, including ventricular septal defect (VSD), truncus arteriosus, aorto-pulmonary window and various types of single ventricle.One staged repair of interrupted aortic arch (IAA) was first described by Barratt-Boyes et al.One-stage repair incorporating direct arch anastomosis was first described by Trusler in 1975.As outcomes of neonatal cardiac surgery have been improved, primary complete repair of IAA and concomitant congenital heart disease in neonatal period has been gradually applied in many institutions. Methods: Retrospective chart review and data base of patients operated for interrupted aortic arch from 2007 to 2016 has been reviewed. Results: 22 patients underwent interrupted aortic arch repiar between 2007 to 2016. Mean Age at the one stage repair was 5 day.Mean age at the second stage repair was 8 months.15 patients(68.1%) were female and 7 patients(31.8%) were male.Di George syndrome was associted in 9 patients(40.9%).Type B (81.9%) was the most common. Mean weight at one stage repair was 3.15 kg at one stage repair.A variety of concmmitent procedures were performed same time including VSD repair in 19 patients( 86.3%), AP window repair in one patient (4.5%), Left pulmonary artery reimplntation in one patient(4.5%) and trucus arteriosus repair in one patient (4.5%).Mean total bypass time and cross clamp time was 174 minutes and 89 minutes respectively.The mean circulatory arrest time was 28 minutes.Postoperative mean ventilatory support was 6 days.The overall mortality was one patient(4.5%). Conclusion: Surgical outcomes for Interrupted aortic arch has significantly improved in last decade. One stage repair with concommitent procedures can be undertaken with good results.